Breakdown of growth front at elevated drawing velocity during directional recrystallization. (4th May 2019) - Yang, Chao; Baker, Ian
ABSTRACT: Cold-rolled, high-purity Ni was directionally annealed at a variety of drawing velocities to understand how columnar grains behave when the drawing velocity was increased during processing. It is shown that the upper limit of drawing velocity for columnar grain propagation is higher than that for columnar grain nucleation in accordance with a prediction of previous modelling (Badmos et al., Acta Materialia, 50 (2002) 8). When the drawing velocity was increased during columnar grain propagation, there are always some columnar grains or some part of a columnar grain that stopped growing, which leads to a breakdown of the growth front. Electron backscatter diffraction showed that the breakdown was either because the growing grains were not the 124 < 211 > orientation with a 40 ∘ / < 111 > misorientation with respect to the cube texture into which the grains were growing, or parts of the columnar grain were locally pinned by low CSL or low-angle misorientation boundaries ahead of them. In general, the growth front breakdown is a result of growth competition.